Kedudukan dan Fungsi Hadis Sebagai Sumber Hukum Islam - Tasbih, Tasbih (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Hadis, as the second source of Islamic law, has ben referred by muslims from the early periode of Islam, in dealing with their both social and sprituai life. Due this reason, many parties, either muslim or non-muslim have used hadis not only in line with proper function as second source after the Qur’an but olso for improper usage. In order to deal with this issue, this article aims at providing a clear analysis on hadis position and its function as a source for Islamic legislation. By reffering to both Qur’anic interpretation ad hadis contents, and also dealing with opinions of Muslim. It is found that hadis is inseparable from the Qur’an. Surely, there has been a point in Islamic history when either certain Muslin or non-Muslim group denied to acknowledge hadis. This denial, however, was due to their iguarance towards the real means of the Qur’an and hadis itself.